2014
DOI: 10.1155/2014/783236
|View full text |Cite
|
Sign up to set email alerts
|

Peganum harmalaL. Intoxication in a Pregnant Woman

Abstract: Peganum harmala L. is a plant widely distributed in the Mediterranean region. It is commonly used in traditional medicine in Morocco as sedative and abortifacient but exposes users to the risk of overdose and poisoning. The pharmacologically active compounds of this plant include a number of β-carboline and quinazoline alkaloids responsible of its pharmacological and toxicological effects. We report the case of a 24-year-old woman, 22 weeks pregnant, intoxicated with the seeds of Peganum harmala L. On admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…The flowering period is March to April and seeds are gathered in the summer [1,6]. The medicinally-active parts of the plant are seeds and roots [1,3,4,7,8]. P. harmala, also known as "Espand" or "Esfand" in Persian [3,4], has been used to ward off the evil eye as an old belief in Iran [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The flowering period is March to April and seeds are gathered in the summer [1,6]. The medicinally-active parts of the plant are seeds and roots [1,3,4,7,8]. P. harmala, also known as "Espand" or "Esfand" in Persian [3,4], has been used to ward off the evil eye as an old belief in Iran [9].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the dried capsules of the plant are hung in some houses to protect against "the evil eye" in some regions of Iran and Turkey [2]. P. harmala is recognized as "Üzerlik" or "Yüzerlik" in Turkey, "Harmel" or "Harmal" in North Africa and Arab countries, and "African Rue", "Syrian rue", "Turkish Rue", and "Mexican Rue" in the United States [1][2][3][4][5][6][7]. For centuries, it has been used to produce a red dye for Persian carpets, and in the 1920s, it was imported into the United States for this purpose [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, harmaline is almost twice as toxic as harmine and in moderate doses causes tremors and clonic convulsions, and sever intoxication occur in cattle, donkeys, sheep and horses . The toxic doses of harmine (rats: 200 mg/kg and mice: 38 mg/kg) are quite different, and the intoxication symptoms are varieties in human and animals . Moreover, studies have showed that all domesticated animals are susceptible to poisoning from Peganum harmala , camels especially cubs that are affected mostly in dry seasons…”
Section: Introductionmentioning
confidence: 99%
“…[14] The toxic doses of harmine (rats: 200 mg/kg and mice: 38 mg/kg) are quite different, and the intoxication symptoms are varieties in human and animals. [15][16][17] Moreover, studies have showed that all domesticated animals are susceptible to poisoning from Peganum harmala, camels especially cubs that are affected mostly in dry seasons. [18] During the past few decades, the in vitro metabolism of harmaline and harmine has already been extensively investigated in some species, for instance, rat, mouse, and human.…”
Section: Introductionmentioning
confidence: 99%